Inherited heterozygous Fanconi anemia gene mutations in a therapy-related CMML patient with a rare NUP98-HOXC11 fusion: A case report - Shen, Kefeng; Zhang, Meilan; Wang, Jiachen; Mu, Wei; Wang, Jin; Wang, Chunyan; Xing, Shugang; Hong, Zhenya; Xiao, Min (Frontiers in Oncology, 2022)
Fanconi anemia (FA) genes play critical roles in the repair of DNA lesions. Non-FA (or underlying FA) patients harboring heterozygous germline FA gene mutations may also face an extremely high risk of developing diverse malformations, inherited bone marrow failure, primary immunodeficiency disease, and hereditary cancer predisposition syndromes. We report a female patient who suffered from ovarian cancer at 50 years of age. During the initial treatment, six cycles of docetaxel and carboplatin (DC) combination chemotherapy were administered followed by two cycles of docetaxel maintenance therapy. Then, she received a routine follow-up every 3 months for the next 3 years, and all the results of the examination and laboratory tests were normal. Unfortunately, at 54 years of age, she developed a secondary cancer of therapy-related (t-) chronic myelomonocytic leukemia (t-CMML). After two courses of a highly intensive induction chemotherapy regimen with DAC (decitabine) and HAA (homoharringtonine, cytarabine), the patient suffered from severe and persistent bone marrow failure (BMF). Targeted next-generation sequencing (NGS) of a panel of 80 genes was performed on her initial bone marrow aspirate sample and identified PTPN11, NRAS, and DNMT3A somatic mutations. In addition, RNA sequencing (RNA-seq) revealed a rare NUP98-HOXC11 fusion. Whole-exome sequencing (WES) verified RAD51C, BRIP1, PALB2, and FANCG heterozygous germline mutations of the FA pathway, which were further confirmed in buccal swab samples by Sanger sequencing. For this patient, we hypothesized that an altered FA pathway resulted in genomic instability, hypersensitivity to DNA-crosslinking agents or cytotoxic chemotherapeutics, and unsuccessful DNA damage repair. Consequently, she developed ovarian cancer and secondary t-CMML and then suffered from BMF and delayed post‑chemotherapy bone marrow recovery after several chemotherapy courses. This case highlights the importance of genetic counseling in patients with hematopoietic neoplasms with high clinical suspicion for carrying cancer susceptibility gene mutations, which requires timely diagnosis and directs personalized management.